Algeria : Selected Economic Issues. (IMF Staff Country Reports; Country Report ;, 1996)
This paper examines institutional reforms in Algeria during the 1990s. A major step toward price liberalization was taken in April 1994, through the abolition of controls on profit margins for most commodities, except for edible oils, sugar, medicines, school supplies, coffee and tobacco, and five cereal products, which were transferred from the category of goods with administered prices to that of goods with controlled profit margins. The paper also reviews the performance of fiscal policy and future prospects for it.